Abnormal Pressure Distribution of Tertiary age formations in Middle & South Iraqi Oil Fields - Almahdawi, Faleh H. M.; Alwan, Kareem A.; Alhusseini, Ahmed K. H. (Journal of Petroleum Research and Studies, 2017)
Prediction of formation pore pressure gradient is a very important factor in designing drilling well program and it help to avoid many problems during drilling operations such as lost circulation, kick, blowout and other problems. In this study, abnormal formation pressure is classified into two types; abnormal high pressure (HP) and abnormal low pressure (LP), therefore any pressure that is either above or below the hydrostatic pressure is referred to as an abnormal formation pressure. This study concerns with abnormal formation pressure distribution and their effect on drilling operations in middle & south Iraqi oil fields. Abnormal formation pressure maps are drawn depending upon drilling evidence and problems. Three formations are considered as abnormal formations in the region of study, these formations geologically existed in Tertiary age and they from shallower to deeper are: Lower Fars, Dammam and Umm Er Radhuma, Formations. The maps of this study referred to either high formations pressure such as (Lower Fars and Umm Er Radhuma) or the low formations pressure such as (Dammam) in middle and south of Iraq. Finally these maps also suggested and showed the area, where no field is drill until now, which may behave as high, low and normal formation pressure for every formation understudy.